Framework for testing the performance of web applications - Eisa, Anwar Habeeb; Mohamed, Mohamed Ali (Journal of engineering sciences and information technology, 2022)
The importance of software testing, particularly performance testing for web applications, is growing with the widespread use of e-commerce applications, where there are many commercial and free tools for conducting performance testing, verifying application service quality standards, and each tool has different features that make it meet certain stages of testing, so it was necessary to integrate these tools in order to reach a comprehensive framework that meets all stages and types of required tests. This research has built a framework that meets all stages and requirements of the testing process by identifying all types of performance tests required, systematically searching for free tools capable of implementing them, and proposing methodologies for work at each stage of the test. The proposed framework PrefTester consists of a tool for managing the testing process PrefTester Manager and two testing tools, GTmetrix & JMeter, in order to benefit from the features of each of them at a testing stage. The test results are more accurate and comprehensive, which will serve as a reference for application developers to study and make possible improvements in order to achieve user satisfaction, reach higher corporate productivity, and achieve more profits.